AB1035 Examination of ultrasound findings in undifferentiated spondyloarthritis patients with dactylitis. (15th June 2017) - Fujikawa, K; Endo, Y; Mizokami, A; Mine, M; Kawakami, A
Abstract : Objectives: To evaluate the ultrasound findings in undifferentiated spondyloarthritis (uSpA) patients with or without dactylitis. Methods: Between April 2014 and December 2016, sixty-six patients with uSpA diagnosed at our center were consecutively enrolled. The diagnosis of uSpA was made by the Japan College of Rheumatology (JCR)-certified rheumatologists and dactylitis was defined as sausage-digit appearance. Ultrasound, clinical and laboratory findings at diagnosis in patients with dactylitis (dactylitis group; n=30) were compared to those without dactylitis (non-dactylitis group; n=36). Grey scale (GS) and power Doppler (PD) signals of the wrist and finger joints, PD signal of extensor and flexor tendon sheaths, and PD signals of the collateral ligament of the fingers in both hands were assessed by ultrasound. Ultrasound assessment was made by JCR-registered sonographers. Results: There were no significant differences in clinical and laboratory findings, including inflammatory back pain, arthritis of the lower limbs, tenderness of the entheses, radiographic/MRI changes of sacroiliac joint and HLA-B27 allele frequency, between two groups. In ultrasound findings, the dactylitis group had significantly more PD signals of the flexor tendon sheaths (83% vs. 22%, p<0.0001), the collateral ligament (83% vs. 25%, p<0.0001), and the MCP joint (30% vs. 3%, p<0.01) as compared with the non-dactylitis group. In logistic regression analysis, the PD signals of the flexor tendons and collateral ligament were independent contributors to a diagnosis of dactylitis (Figure 1 ). Conclusions: Development of active inflammation of enthesis organ determined by ultrasound is supposed to associate importantly with the judgment as dactylitis in patients with uSpA. Disclosure of Interest: None declared